Conference Record of the the 2002 IEEE International Symposium on Electrical Insulation (Cat. No.02CH37316)
DOI: 10.1109/elinsl.2002.995955
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of epoxy-organically modified layered silicate nanocomposites

Abstract: Epoxy-silicate nanocomposites were prepared by dispersing synthetic layered silicates modified with alkylammonium ions. In the dispersing process, the organically modified layered silicates were mixed in epoxy resin with shearing, and aggregations of the silicates were removed by centrifugal separation after mixing epoxy resin and silicates. Micrographs taken by transmission electron microscopy (TEM) indicate that the nanocomposites have a mixed morphology including both parallel silicate layers (0.1-0.5cun, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
2

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 7 publications
5
38
0
2
Order By: Relevance
“…Regarding the large increase in the storage modulus in a rubbery state region based on these results, it can be definitely considered that the homogeneous dispersion and the excellent interfacial coupling force in a mixture state of the micro and nano particles limits the mobility of the epoxy molecules [10][11][12][13]. This can be detected in the cross-linking density.…”
Section: The Dmamentioning
confidence: 99%
“…Regarding the large increase in the storage modulus in a rubbery state region based on these results, it can be definitely considered that the homogeneous dispersion and the excellent interfacial coupling force in a mixture state of the micro and nano particles limits the mobility of the epoxy molecules [10][11][12][13]. This can be detected in the cross-linking density.…”
Section: The Dmamentioning
confidence: 99%
“…Moreover, for the former the peak amplitude is much larger. Previous investigations (6) showed that a 6%wt EVA-Somasif microcomposite (obtained with a not compatibilised clay) does not Fig. 1.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…Nanodielectrics have attracted a great attention since the first experimental data were reported publicly in 2002 [10][11]. The current research is concentrated on the short-term breakdown and the long-term failure of epoxy and other polymer matrix with inorganic nanoparticles added.…”
Section: Introductionmentioning
confidence: 99%